Transition metal abundance as a key parameter for the search of Life in the Universe - Giovanni Covone; Donato Giovannelli (The Open Journal of Astrophysics)
The search for Life in the Universe generally assumes three basic life's needs: I) building block elements (i.e., CHNOPS), II) a solvent to life's reactions (generally, liquid water) and III) a thermodynamic disequilibrium. It is assumed that similar requirements might be universal in the Cosmos. On our planet, life is able to harvest energy from a wide array of thermodynamic disequilibria, generally in the form of redox disequilibrium. The amount of different redox couples used by living systems has been estimated to be in the range of several thousands of reactions. Each of these energy yielding reactions requires specialised proteins called oxidoreductases, that have one or more metal cofactors acting as catalytic centres to exchange electrons. These metals are de facto the key component of the engines that life uses to tap into the thermodynamic disequilibria needed to fuel metabolism. The availability of these transition metals is not uniform in the Universe, and it is a function of the distribution (in time and space) of complex dynamics. Despite this, Life's need for specific metals to access thermodynamic disequilibria has been so far completely overlooked in identifying astrobiological targets. We argue that the availability of at least some transition elements appears to be an essential feature of habitability, and should be considered a primary requisite in selecting exoplanetary targets in the search for life.